'No more occasion for Puffendorf nor Hugo Grotius': the Spanish rights of possession in America and the Darien venture (1698–1701). Issue 4 (19th May 2021) - Lista, Giovanni
ABSTRACT: Set within the framework of international intellectual history, the present article focusses on the propaganda campaign undertaken by the Company of Scotland to prove the legality of its settlement in the Darien province. It first shows how a group of Scottish authors appropriated sixteenth-century natural law arguments from Spanish sources to reject the claims based on the Bulls of Donation and conquest, which underpinned Spain's sovereignty over its American territories. Acting individually and collectively, anonymously and under pseudonyms, pro-Darien propagandists instrumentally quoted and restated the contents of major works from Francisco de Vitoria and Bartolomé de Las Casas. Additionally, the Scots also deployed the theories elaborated by Hugo Grotius and Samuel Pufendorf to refute discovery and occupation as further means of acquisition of American lands. In contrast with Spanish expansionism, the Scottish colony eventually grounded its claims on the consent of the indigenous Cuna rulers and on the official treaties recognizing the latter's sovereignty over Darien, emulating the Dutch commercial model of empire and colonial practices.